Politisation des étudiant·es en France, à l’aune de l’épidémie de Covid-19 - Maxime Salehein (Sociétés et Jeunesses en Difficulté)
The Covid-19 epidemic had equivocal effects on the various political socializations of higher education students in France. The health crisis, far from having a depoliticizing effect, reinforced political dispositions, and even created new ones. The delegitimization of institutional political forms is valid for most of students questioned. Yet, it is the students the most severely affected by sanitary restrictions, who are also the most precarious, who report an accelerated politicization with revendications.